Éradiquer l’homosexualité en prison - Quentin Markarian (Criminocorpus)
The principle of cell imprisonment was introduced into French law on the 5th of June 1875. Inextricably linked to the nineteenth century reform of the penitentiary system, this model of imprisonment aimed to replace collective dormitories with individual cells. From the Restoration to the Third Republic, this shift in regime was supported for its ability to eradicate homosexuality in prison. The sexual obsession and panic provoked by the “capital vice of communal dormitories” are especially evident in the writings of penal science, government inquiries, as well as parliamentary works and debates that gave rise to the law of June 5, 1875. Historically built on a heteronormative discourse, the cell remains a legal and architectural pillar of contemporary penal prisons.